Myśl polityczna Jacka Kuronia - Madera, Andrzej Józef (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2003)
The paper analyzes an attempt at the reconstruction of political thinking and activities of Jacek Kuroń in 1964–1993.We shall take a look at the evolution of our protagonist’s outlook of life from a Marxist to a supporter of the social market economy and at the process of his shaping a set of ideas, values and views that describe his contemporary political thought. The historic background, activities of opposition groups, the organization and activity of political opposition in the People’s Republic of Poland are only outlined to an extent that was necessary in order to place the political platforms discussed and analyzed. The basic sources for the research are memoir publications, program documents and the abundance of press publications by Jacek Kuroń.